Evidence on the Impact of Education on Innovation and Productivity - Martin Junge; Battista Severgnini; Anders Sørensen (Copenhagen Business School (CBS), Department of Economics, 2012)
This paper investigates the importance of the educational mix of employees at the rm level for the probability of rms being involved in innovation activities. We distinguish between four types of innovation: product, process, organisational, and marketing innovation. Moreover, we consider three di erent types of education for employees with at least 16 years of schooling: technical sciences, social sciences, and humanities. Furthermore, we examine the in uence of these di erent innovation activities on rm productivity. Using a rotating panel data sample of Danish rms, we nd that di erent types of innovations are related to distinct educational types. Moreover, we nd that rms that adopt product and marketing innovation are more productive than rms that adopt product innovation but not marketing innovation and rms that adopt marketing innovation but not product innovation. In addition, rms that adopt organisational and process innovation demonstrate greated productivity levels than forms that adopt organisational innovation but not process innovation that again demonstrate greater productivity than rms that do not adopt process innovation but not organisational innovation. Finally, we establish that product and marketing innovation as well as organisational and process innovation are complementary inputs using formal tests for supermodularity. Complementarity can be rejected for all other pairs of innovation types.
hdl:10398/8498
Keywords: D24; J24; O31; O32; 330; educational composition; human capital; innovation; productivity; complementarity